Comparison of the nematode-controlling effectiveness of 10 different essential oilencapsulated lipid nanoemulsions - Nguyễn, Thị Huỳnh Nga (2022)
This study aimed to compare nematode-controlling effectiveness of lipid-based nanoemulsions (LNs) encapsulating 10 different common essential oils (EOs). These 10 EO-LNs were successfully prepared by a combined method of homogenization and sonication with a small particle size (less than 150 nm), a small PDI, a high zeta potential and a high storage stability. The results indicated that all the 10 EO-LNs, while showing no phytotoxicity, exhibited high nematode-controlling effectiveness of 2 to 5 times higher compared to that of their corresponding native EO (oil form). In addition, LNs encapsulating mustard oil (NaMus), cinnamon oil (NaCin), garlic oil (NaGar), and Java lemongrass oil (NaJlg) gave the highest nematode-controlling effectiveness with C index value at 400 times dilution of 49.75%, 33.61%, 22.98% and 16.71%, respectively. Exhibiting such potential, alongside the affordable price of materials, NaMus, NaJlg and NaCin can be widely applied in sustainable horticulture to protect plants from nematodes.